Paulista registry of glomerulonephritis: 5-year data report - Malafronte, Patricia; Mastroianni-Kirsztajn, Gianna; Betonico, Gustavo N.; Egidio Romao, Joao; Alves, Maria Almerinda R.; Carvalho, Maria Fernanda; Viera Neto, Osvaldo M.; Cadaval, Ricardo A. M.; Bergamo, Ronaldo R.; Woronik, Viktoria; Sens, Yvoty A. S.; Marrocos, Mauro S. M.; et al. (Oxford University Press, 2006)
Background. The Paulista Registry of Glomerulopathies was created in May 1999 and comprises several centres of São Paulo, the most populous Brazilian State, that concentrates people from all regions of the country who look for health care.Methods. This report includes data from 2086 patients from Brazil submitted to renal biopsy due to the presumed diagnosis of glomerular diseases, registered prospectively since May 1999 until January 2005. Data were collected by the integrants of the 11 centres involved, utilizing a standardized questionnaire.Results. The mean age of the patients was 34.5 +/- 14.6 years. Primary glomerular diseases were more frequent in males (55.1%) than in females; on the other hand, secondary glomerular diseases were more frequent in females (71.8%). The most common clinical presentation was nephrotic syndrome and the frequency of hypertension, at this time, was 55.5%. There was a predominance of indication of biopsies in the third, fourth and fifth decades of life. The most common primary glomerular diseases were focal and segmental glomerulosclerosis (29.7%), followed by membranous nephropathy (20.7%), IgA nephropathy (17.8%), minimal change disease (9.1%), membranoproliferative glomerulonephritis (7%), crescentic glomerulonephritis (4.1%), advanced chronic glomerulopathy (4%), non-IgA mesangial glomerulonephritis (3.8%), diffuse proliferative glomerulonephritis (2.5%), focal segmental proliferative glomerulonephritis (1%) and others (0.3%). The most frequent secondary glomerular disease was lupus nephritis, corresponding to 66.2% of the cases, followed by post-infectious glomerulonephritis (12.5%), diabetic nephropathy (6.2%), diseases associated to paraproteinaemia (4.9%), hereditary diseases (4.6%), vasculitis (3.2%), malignancies (0.9.%), secondary focal segmental glomerulosclerosis (0.6%) and others (0.9%).Conclusion. Focal segmental glomerulosclerosis was the most frequent primary glomerular disease, followed by membranous nephropathy and IgA nephropathy. Lupus nephritis predominated over all the other secondary glomerular diseases.
Keywords: Brazilian registry; epidemiology; glomerulopathy